THE EFFECT OF SAFE COSMETIC COUNSELINGTO KNOWLEDGE AND ATTITUDE OF STUDENTS OF STATE SENIOR HIGH SCHOOL 3 GORONTALO - Prisca Safriani Wicita (LP2M Universitas Bina Mandiri Gorontalo, 2019)
Cosmetics are materials or preparations intended to be used on the outside of the human body (epidermis, hair, nails, lips and external genital organs) or teeth and oral mucous membranes primarily to cleanse, fragrance, change the appearance and / or improve body odor or protect or maintain the body in good condition Cosmetics is one product that is used routinely and continuously by the public. Therefore, in the selection of cosmetics required a vigilance of the components contained therein, especially those containing additives. Negative reactions caused not only affect the skin tissue but also affect the tissue system and other important organs. The lack of understanding and the lack of optimal socialization about safe cosmetics are the main factors, in this case, therefore one of the efforts that can be done to increase adolescent knowledge is to conduct counseling activities. Department of Pharmacy of the Polytechnic of the Ministry of Health Gorontalo in collaboration with IAI Gorontalo City, conducting counseling for students of State Senior High School 3 Gorontalo. The purpose of this activity is to see the effect of counseling on improving the knowledge and attitudes of students of State Senior High School 3 Gorontalo about safe cosmetics. This research with pre-experiment design uses a pretest-posttest design model that is analyzed by the Wilcoxon sign test. The results of the analysis of differences in mean knowledge and attitudes of students showed results, there were significant differences in the knowledge and attitudes of students where the value of p <0.0001 (p <0.05) and based on the value of the proportion of knowledge before counseling and after counseling there was an increase in the number and percentage where the value of p <0.0001 (p <0.05), but based on the results of the analysis for the proportion of attitudes there was no significant difference in the attitudes of students p = 0.163 (p> 0.05). Overall, these results indicate that counseling can bring changes in knowledge and attitudes towards students of State Senior High School 3 Gorontalo so that it is expected to be able to improve health problems such as skin diseases, especially those related to the use of illegal cosmetics